2x+11y-4xi=14+16i

Simple and best practice solution for 2x+11y-4xi=14+16i equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+11y-4xi=14+16i equation:


Simplifying
2x + 11y + -4xi = 14 + 16i

Reorder the terms:
-4ix + 2x + 11y = 14 + 16i

Solving
-4ix + 2x + 11y = 14 + 16i

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-16i' to each side of the equation.
-4ix + 2x + -16i + 11y = 14 + 16i + -16i

Reorder the terms:
-16i + -4ix + 2x + 11y = 14 + 16i + -16i

Combine like terms: 16i + -16i = 0
-16i + -4ix + 2x + 11y = 14 + 0
-16i + -4ix + 2x + 11y = 14

Add '-2x' to each side of the equation.
-16i + -4ix + 2x + -2x + 11y = 14 + -2x

Combine like terms: 2x + -2x = 0
-16i + -4ix + 0 + 11y = 14 + -2x
-16i + -4ix + 11y = 14 + -2x

Add '-11y' to each side of the equation.
-16i + -4ix + 11y + -11y = 14 + -2x + -11y

Combine like terms: 11y + -11y = 0
-16i + -4ix + 0 = 14 + -2x + -11y
-16i + -4ix = 14 + -2x + -11y

Reorder the terms:
-14 + -16i + -4ix + 2x + 11y = 14 + -2x + -11y + -14 + 2x + 11y

Reorder the terms:
-14 + -16i + -4ix + 2x + 11y = 14 + -14 + -2x + 2x + -11y + 11y

Combine like terms: 14 + -14 = 0
-14 + -16i + -4ix + 2x + 11y = 0 + -2x + 2x + -11y + 11y
-14 + -16i + -4ix + 2x + 11y = -2x + 2x + -11y + 11y

Combine like terms: -2x + 2x = 0
-14 + -16i + -4ix + 2x + 11y = 0 + -11y + 11y
-14 + -16i + -4ix + 2x + 11y = -11y + 11y

Combine like terms: -11y + 11y = 0
-14 + -16i + -4ix + 2x + 11y = 0

The solution to this equation could not be determined.

See similar equations:

| 7(2x+3)=21 | | (2x+7)(5x-4)=0 | | (x+0.9)(x+2.6)=0 | | (2n-1)/3-1/2=17/2 | | (2n-1)/3-1/5=17/5 | | 4[x+2]=18 | | X^5-x^4-1=0 | | 6(x+8)-29= | | 191+13x=360 | | 15x-12=49 | | 140/2000 | | 16x^2-24x-23=0 | | 8(x+4)-3= | | b+40+b+26=9b+5 | | -2(5x+13)-2=-6(3x-2)-41 | | 3[x-1]=49 | | 5(z+4)+1=7-(z+4) | | 12x^2-30x+48=0 | | A^2+15+54=0 | | -7=9+4c | | x-6y=50 | | t/-4-11 | | 2n/3=20/2 | | 58=4-9x | | 4s+8s= | | 5/(3x)^-4=? | | 5/(3x)^-4= | | 2Sin(X-10)=0.8 | | 2n/3=10/2 | | 5/(3x)^-4 | | 32x^2+76x-91=0 | | -4(6n-6)+4= |

Equations solver categories